AB0444 Effect of rituximab on a salivary gland ultrasound score in primary sjÖgren's syndrome: results of the tractiss multicentre randomised trial sub-study. (15th June 2017) - Fisher, BA; Everett, CC; Rout, J; O'Dywer, JL; Emery, P; Pitzalis, C; Ng, W-F; Carr, A; Pease, CT; Price, EJ; Sutcliffe, N; Makdissi, J; et al.
Abstract : Background: B lymphocytes are important in the pathogenesis of primary Sjögren's syndrome (PSS), but two phase III trials (TEARS and TRACTISS) of the B cell depleting agent rituximab (RTX) failed to show an effect on their primary endpoints in PSS. Whilst RTX may lack efficacy in a non-stratified PSS population, other possible explanations for these negative results include the choice and timing of primary outcome. In a small single-site salivary gland ultrasound (SGUS) substudy in TEARS, more subjects in the RTX arm demonstrated improvement in parotid gland echostructure. Importantly, SGUS is an operator-dependent technique. Objectives: To compare the effects of RTX versus placebo on SGUS in PSS, in a multicentre, multiobserver substudy of TRACTISS. Methods: Subjects consenting to SGUS were randomised to 1000mg RTX or placebo given at weeks 0, 2, 24 and 26, and scanned at baseline and weeks 16 and 48. Sonographers completed a 0–11 total ultrasound score (TUS) comprising domains of echogenicity, homogeneity, glandular definition, glands involved, and size of hypoechoic foci. Baseline-adjusted values of TUS were analysed over time, modelling change from baseline at each time point. For each TUS domain we fitted a repeated measures logistic regression model to model the odds of a response in the RTX arm (defined as a 1 point improvement) as a function of the baseline score, age category, disease duration and time point. Results: 66 patients (49.6% of the total study population) consented to SGUS, and 52 (39.1%; n=26 RTX and n=26 placebo) completed the baseline and at least one follow-up visit. Estimated baseline-adjusted TUS at week 16 was 6.2 (95% CI 5.4–7.0) for placebo and 5.0 (95% CI 4.4–5.6) for RTX, and at week 48, 6.1 (95% CI 5.5–6.6) and 4.8 (95% CI 4.2–5.4) respectively. Estimated between group differences (RTX-placebo) in baseline adjusted TUS were -1.2 (95% CI -2.1 to -0.3; p=0.0099) and -1.2 (95% CI -2.0 to –0.5; p=0.0023) at weeks 16 and 48. Glandular definition was the only domain to show statistically significant improvement with an OR of 6.8 (95% CI 1.1–43.0; p=0.043) at week 16 and 10.3 (95% CI 1.0–105.9; p=0.050) at week 48. Improvement of ≥1 point in TUS was associated with improvement in oral dryness VAS at week 16 (diff=15.9; CI 1.5 to 30.3; p=0.030) but not week 48 in the RTX arm. Conclusions: TUS differed between study arms, favouring RTX. This encourages further research into SGUS as an imaging biomarker in PSS clinical trials. Acknowledgements: Funded by Arthritis Research UK. Roche provided RTX. Disclosure of Interest: B. Fisher Paid instructor for: Novartis, Roche, Virtualscopics, C. Everett: None declared, J. Rout: None declared, J. O'Dywer: None declared, P. Emery: None declared, C. Pitzalis: None declared, W.-F. Ng Consultant for: Pfizer, UCB, MedImmune, Takeda and Sanofi, A. Carr: None declared, C. Pease: None declared, E. Price: None declared, N. Sutcliffe: None declared, J. Makdissi: None declared, N. Gendi: None declared, F. Hall: None declared, S. Ruddock: None declared, C. Fernandez: None declared, C. Hulme: None declared, K. Davies: None declared, C. Edwards: None declared, P. Lanyon: None declared, R. Moots: None declared, E. Roussou: None declared, L. Sharples: None declared, M. Bombardieri Consultant for: GSK, Amgen/MedImmune and UCB, S. Bowman Consultant for: Cellgene, Glenmark, GSK, Eli Lilly, Novartis, Roche, Takeda, UCB